Heat Shock Protein 27 Is an Emerging Predictor of Contrast-Induced Acute Kidney Injury on Patients Subjected to Percutaneous Coronary Interventions - Andrzej Jaroszyński; Tomasz Zaborowski; Stanisław Głuszek; Tomasz Zapolski; Marcin Sadowski; Wojciech Załuska; Anna Cedro; Teresa Małecka-Massalska; Wojciech Dąbrowski (Cells, 2021)
Contrast-induced acute kidney injury (CI-AKI) is a serious complication associated with considerable morbidity and mortality. Heat-shock protein 27 (HSP27) plays a role in the defense of the kidney tissue against various forms of cellular stress, including hypoxia and oxydative stress, both features associated with CI-AKI. The aim of our study was to evaluate a potential predictive value of HSP27 for CI-AKI in patients subjected to percutaneous coronary interventions (PCI). Included were 343 selected patients subjected to PCI. Exclusion criteria were conditions that potentially might influence HSP27 levels. HSP27 serum levels were evaluated prior to PCI, together with serum creatinine, the concentration of which was also evaluated twice at 48 and 72 h post PCI. CI-AKI was diagnosed in 9.3% of patients. Patients in whom CI-AKI was diagnosed were older (p < 0.001), were more often females (p = 0.021), had higher prevalence of diabetes (p = 0.011), hypotension during PCI (p < 0.001), albuminuria (p = 0.004) as well as multivessel disease (p = 0.002), received higher contrast volume (p = 0.006), more often received contrast volume (CV) above the maximum allowed contrast dose (MACD) (p < 0.001), and had lower HSP27 level (p < 0.001). On multivariate analysis, CV > MACD (OR 1.23, p = 0.001), number of diseased vessels (OR 1.27, p = 0.006), and HSP27 (OR 0.81, p = 0.001) remained independent predictors of CI-AKI. Low concentration of HSP27 is an emerging, strong and independent predictor of CI-AKI in patients subjected to PCI.